KANDUNGAN NUTRIEN SILASE BUAH SEMU JAMBU METE SEBAGAI PAKAN PADA BERBAGAI LEVEL TEPUNG GAPLEK DAN LAMA PEMERAMAN - Berdeta Barek Koten (Politeknik Pertanian Negeri Kupang, 2010)
Nutritive Value Of Chestnut Fruit (Anacardium Occidentale) Silage In Combination With Various Levels Of Cassava Mill Addition and Length Of Fermentation Time As Feed. The aim of this experiment was to evaluate nutritive value of chestnut fruit silage in combination with various levels of casava mill addition and length of fermentation time. This research was conducted in 2 treatment factors with 3 replication. The I factor are : Various level of casava mill e.i. L1: 0%, L2 : 3%, L3 : 6% and L4 : 9%, and the II factor are length of fermentation time e.i W1 : 20 days, W2 : 40 days and W3 : 60 days. The result showed that silage technonogy manifestly (P<0,05) with various casava mill level and fermentation time can increase nutritive value chestnut fruit. Higher organic mater percen at 0% casava mill with fermentation time of 20 days (97,94%). Higher ash percen at 0% casava mill with fermentation time of 40 days (97,94%), and at 3% casava mill with fermentation time of 60 days (3,67%). Higher crude fiber at 9% casava mill with fermentation time of 60 days (7,19%) and low at 0% casava mill with fermentation time of 20 days (6,29%). Higher extract ether at 3% casava mill with fermentation time of 40 days (3,73%) and at 6% casava mill with fermentation time of 40 days (3,38%). It could be concluded that silage technonogy can be aplication at chestnut fruit. This technology can increase benefit of chestnut fruit as feed because increase its nutritive value.Keywords: Silage, Chestnut fruit, Casava mill, Fermentation time, nutritive value